Material handling system modeling of a modern FAB - Lee, Kwan W.; Chang, Dae S.; Park, Sang C. (ACM International Conference Proceeding Series, 2018)
This paper presents a modeling methodology for a material handling system of a modern FAB. These days, a system of the modern FAB is complex owing to reentrant process characteristic of the semiconductor FAB process. This research introduces briefly about AMHS and the notion about DEV&DESS (Discrete Event System and Differential Equation System Specification). It presents the OHT (Overhead Hoist Transport) movement model has described using the DEV&DESS formalism. The reason for using DEV&DESS in this research is that it is suitable formalism to describe complex systems. Specially, we had to avoid a collision between OHT vehicles while performing a simulation. Finally, it shows the implementation result of the OHT in sample semiconductor FAB model to validate a model which we had modeled.
Keywords: Differential equation systems; Material handling systems; Model and simulation; Modeling methodology; Movement model; Overhead hoist transports; Process characteristics; Semiconductor fabs; DEV&DESS; Modeling and Simulation; Semiconductor FAB Overhead Hoist Transport